PENGARUH KUALITAS PELAYANAN DAN FAKTOR KEAMANAN DATA PRIBADI TERHADAP TINGKAT KEPERCAYAAN MASYARAKAT PENGGUNA APLIKASI JAKEVO DI KELURAHAN ROROTAN - Afrina, Faradila Rima; Islah, Khikmatul (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
There are still limitations in studying simultaneously or significantly on the influence of service quality, security factors on trust public. So this research aims to analyze the influence significant or simultaneous between service quality and safety factors public trust. The object of this research is the Jakevo application as novelty in research. Research approach used in research this is a quantitative approach. Data obtained from this approach collected through structured instruments, such as questionnaires or surveys. T test results shows that service quality has a significant effect on trust society (sig. 0.000 < 0.05) with a coefficient of 1.984. F test confirms that both together have a significant effect on trust society (sig. 0.000 < 0.05) F count 99.926 F table 3.09. dertamination coefficient (R Square) of 0.598 shows that 59.8% of public trust is influenced by these two variables, while 40.2% is influenced by other factors.